Physico-chemical analysis of spring and river waters from Brgy. Tag-osip, Buruanga, Aklan. - Figueroa, Eugene G. (2006.)
Six sampling sites were selected that are sources of water in Brgy. Tag-osip, Buruanga, Aklan. Water are analyzed in order to determine its suitability in agricultural and domestic purposes based on EEC, EPA, WHO, and Canadian Water Quality Guidelines., The results show that the total alkalinity ranges from 11.6 to 146.0 mg/L CaCO3 indicating the presence of bicarbonates in measurable amount in all samples. Acidity ranges from 6.4 to 21.2 mg/L CaCO3. Results of hardness analysis show that the samples are soft waters and values range from 4.0 to 58.4 mg/L CaCO3. The dissolved oxygen ranges from 5.37 to 12.66 mg/L O2 and this shows that the water in all sites is capable to support aquatic organisms. Phosphorus concentration is from 0.027 to 0.195 mg/L PO4 -P. Chloride concentration in all sites ranges from 1.78 to 20.77 mg/L. Evaporation residue values are low which range from 2.5 to 123.3 mg/L. The nitrate concentrations of all the samples (0 to 493 ppb) are low considering that plants can utilize only 100 to 400 ppm nitrogen. Potassium concentrations in all sites are in the range of very neglible amount (not detected) to 2.0295 mg/L. Iron concentration ranges from nd (not detected) to 5.1139 mg/L. In the three samplings done, lead concentration is present which ranges from nd to 0.1486 mg/L. However, Cadmium and Chromium in the three samplings are all below detection. The results indicate that the water from the six sites are significantly different and are within the limits for agricultural purposes. The value of lead concentration that exceeded the maximum contaminant level of 0.015 mg/L, poses threat to health.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Waters -- Spring -- Brgy. Tag-osip, Buruanga, Aklan; Waters -- Rivers -- Brgy. Tag-osip, Buruanga, Aklan